Remittances to Mexico. Macroeconomic and microeconomic uses - Isidro Luna, Víctor; López Vega, Rafael (SUMMA, 2023)
This article discusses the macroeconomic and microeconomic characteristics of Mexican remittances from 2003 to the present day. To study the macroeconomic relevance of remittances, we use the Bank of Mexico (Banxico) balance of payments from a heterodox viewpoint, and to study microeconomic relevance, we rely on the survey of international migration at the north border (EMIF Norte) regarding the flow of inland migrants coming from the United States (Procedentes de Estados Unidos-Terrestres, PEUAT). Macroeconomically, remittances are a stable flow of foreign change. They have blocked the existence of an unsustainable current account deficit and prevented crises and exchange rate depreciations. Microeconomically, remittances are national purchasing power, and they serve to increase private consumption in very important areas such as food and clothing, and health care and to reflect demographic characteristics of the remittances’ senders, such as the type of migrant who sends remittances (resident or nonresident), the sex of the migrant, and the main factors that drive remittances sent by Mexican people who are residents on US soil. This article does not fully show interconnections between the macroeconomic and microeconomics uses of remittances, nor does it stress the discrepancy between the balance of payments and national surveys in accounting for familiar remittances. Rather, we underline that a combination of sources such as the national accounts and national surveys must be carried out to understand the effects of remittances from macroeconomic and microeconomic viewpoints.